2022
DOI: 10.3390/antiox11101848
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antioxidative, Anti-Inflammatory, and Antimelanogenic Effects of Fermented Hydroponic Ginseng with Bacillus Strains

Abstract: Compared with traditionally cultured ginseng, hydroponic ginseng (HG) contains more remarkable bioactive compounds, which are known to exert diverse functional effects. This study aimed to enhance the multifunctional effects, including the antioxidative, anti-inflammatory, and antimelanogenic effects, exhibited by fermented HG with Bacillus strains, such as Bacillus subtilis KU43, Bacillus subtilis KU201, Bacillus polyfermenticus SCD, and Bacillus polyfermenticus KU3, at 37 °C for 48 h. After fermentation by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Therefore, in this study, we tried to verify the skin-whitening effect of maca root. Especially, fermented plant extracts have better antioxidant, anti-melanogenic, anti-inflammatory, and anti-wrinkle effects compared with non-fermented plant extracts [ 66 , 67 , 68 , 69 ]. Fermented red ginseng showed whitening and anti-wrinkle effects [ 70 ], whereas fermented Fructus acrtii extracts suppressed the expression of MMP-1 in human fibroblasts (HDFs), and fermented hydroponic ginseng showed improved antioxidant, anti-inflammatory, and anti-melanin production [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study, we tried to verify the skin-whitening effect of maca root. Especially, fermented plant extracts have better antioxidant, anti-melanogenic, anti-inflammatory, and anti-wrinkle effects compared with non-fermented plant extracts [ 66 , 67 , 68 , 69 ]. Fermented red ginseng showed whitening and anti-wrinkle effects [ 70 ], whereas fermented Fructus acrtii extracts suppressed the expression of MMP-1 in human fibroblasts (HDFs), and fermented hydroponic ginseng showed improved antioxidant, anti-inflammatory, and anti-melanin production [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, fermented plant extracts have better antioxidant, anti-melanogenic, anti-inflammatory, and anti-wrinkle effects compared with non-fermented plant extracts [ 66 , 67 , 68 , 69 ]. Fermented red ginseng showed whitening and anti-wrinkle effects [ 70 ], whereas fermented Fructus acrtii extracts suppressed the expression of MMP-1 in human fibroblasts (HDFs), and fermented hydroponic ginseng showed improved antioxidant, anti-inflammatory, and anti-melanin production [ 67 ]. Furthermore, fermented unpolished black rice ( Oryza sativa L.) and fermented Viola mandshurica inhibited melanogenesis in B16F10 [ 71 , 72 ], while fermented soybean extracts showed higher antioxidant and skin-whitening effects than those in a non-fermented condition [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is very interesting to underline that melanin is one of the few materials that is already present in organisms in the form of nanoaggregates. Although the AOX properties of natural melanin are well documented [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], and in addition to the ubiquitous presence of melanin in nature, its most recent and promising application is based on the development of synthetic analogs [ 78 ]. The main reason for this is that melanin-like materials can be easily produced from low cost and biocompatible precursors via very versatile and environmentally friendly processes [ 79 , 80 ].…”
Section: Aox Properties Of Melanin Npmentioning
confidence: 99%
“…It is reported that more than 90 ginseng peptides with potential biological activities based on MS-based data mining and sequencing have been identified . In recent years, an increasing number of GOPs have been identified through HPLC-MS as known amino acid sequences with good antioxidant, antiaging, memory-improving, anti-inflammatory, and lipid-lowering effects. Besides, GOPs have the ability to extend the lifespan of Caenorhabditis elegans cultured in cholesterol-feeding media and can suppress cellular senescence induced by oxidative stress via the NAD + /SIRT1/PGC-1α pathway. The monomers of ginseng peptides, ITGYAP, LTGYAP, ITGYPA, and LTGYPA, have also been proven to delay neurodegenerative disease, AD, caused by oxidative stress . In view of the excellent antioxidant and antiaging properties of ginseng peptides, we have selected the hexapeptide of plant origin, EHGEYE, which also has strong anti-inflammatory properties. ,,, …”
Section: Introductionmentioning
confidence: 99%